DISCURSO DOCENTE NO CURSO DE LETRAS: UMA ANÁLISE DE AVALIATIVIDADE - Almeida, Fabíola Aparecida Sartin Dutra Parreira (Intercâmbio, 2010)
This study aims at presenting the analysis of spoken discourse of a teacher from college in the moment she interacts with her student based on the appraisal framework, focusing on how the appraisal category-affect is evidenced in the teachers’ discourse and its implications in the process of interaction between teacher-student.